1999
DOI: 10.1093/ageing/28.5.429
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of outcome on admission to an acute geriatric ward

Abstract: Limited activities of daily living and geriatric problems on admission are the strongest predictive factors of outcome, independent of diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
71
2
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 12 publications
15
71
2
9
Order By: Relevance
“…In the study of Laniece et al functional disability was relevant to explain the risk of early readmissions in a cohort of patients aged 75 and older [23]. However, in this study, functional disability as assessed by the Barthel index was not associated with readmission, in agreement with the findings of Alarcon et al, who showed that limited activities of daily living were only predictive of hospital mortality and prolonged stay [24].…”
Section: Discussionsupporting
confidence: 89%
“…In the study of Laniece et al functional disability was relevant to explain the risk of early readmissions in a cohort of patients aged 75 and older [23]. However, in this study, functional disability as assessed by the Barthel index was not associated with readmission, in agreement with the findings of Alarcon et al, who showed that limited activities of daily living were only predictive of hospital mortality and prolonged stay [24].…”
Section: Discussionsupporting
confidence: 89%
“…Studies exploring polypharmacy have been conducted in different clinical settings, in out-patients/ambulatory patients (14,25,(30)(31)(32)(33), hospitalised patients (26,(34)(35)(36), patients in nursing homes (37,38), and elderly patients (25)(26)(27)32,33,39). Studies have also been performed based on data from prescription or population databases (13,28,(40)(41)(42).…”
Section: Frequency Of Polypharmacymentioning
confidence: 99%
“…Studies have shown that the use of many drugs is connected to negative health outcomes such as adverse drug reactions, interactions, poor patient adherence and hospitalisations (10,17,19,26,32,(45)(46)(47)(48)(49). We have previously shown that the number of drugs on admission to hospital is an independent risk factor for the occurrence of drug-related problems, like for example wrong drug choice, non-optimal dosage, adverse drug reactions, drug interactions and non-adherence (50).…”
Section: Consequences Of Polypharmacymentioning
confidence: 99%
“…Alguns autores consideram que a desnutrição pode ser difícil de distinguir das alterações resultantes do processo natural do envelhecimento (62,63), porém se não for detectada, pode resultar em agravamento de condições clínicas e aumento da mortalidade (62). A população idosa é particularmente propensa a problemas nutricionais devido a fatores relacionados com as alterações fisiológicas e sociais, ocorrência de doença crônica, uso de várias medicações, problemas na alimentação (comprometendo a mastigação e deglutição), depressão e alterações da mobilidade com dependência funcional (62,64,65).…”
Section: Aspectos Peculiares Do Idosounclassified